2021
DOI: 10.1002/rrq.411
|View full text |Cite
|
Sign up to set email alerts
|

The Science of Reading Progresses: Communicating Advances Beyond the Simple View of Reading

Abstract: The simple view of reading is commonly presented to educators in professional development about the science of reading. The simple view is a useful tool for conveying the undeniable importance—in fact, the necessity—of both decoding and linguistic comprehension for reading. Research in the 35 years since the theory was proposed has revealed additional understandings about reading. In this article, we synthesize research documenting three of these advances: (1) Reading difficulties have a number of causes, not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
125
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(202 citation statements)
references
References 125 publications
(174 reference statements)
2
125
1
4
Order By: Relevance
“…While we concur that there has been substantial progress made in understanding reading over the last 35 years, we reject the claims that the SVR has been disproven by this progress and that it no longer provides a useful, theoretically sound, and empirically supported model of reading. Furthermore, we reject the claims that the proposed alternative to the SVR offered by Duke and Cartwright (2021) is superior (either theoretically or empirically), and that it represents an advancement in pedagogical utility. In this comment on Duke and Cartwright’s (2021) central claims, we discuss (1) the authors’ view of the SVR (addressing issues about what it models, the distinctions it embodies between proximal and distal factors, and its utility for practitioners); (2) the authors’ claims that three advances in reading research invalidate the SVR (namely, the causes of reading difficulty within and beyond the SVR’s two factors of word recognition and language comprehension, 1 the overlap between measures of these two factors and the bridge skills claimed to be supported on the basis of such overlap, and the role of active self‐regulation in reading); and (3) the authors’ summary conclusion that the SVR, and any other expanded models of reading based on it, must be rejected because of these advances.…”
contrasting
confidence: 64%
See 1 more Smart Citation
“…While we concur that there has been substantial progress made in understanding reading over the last 35 years, we reject the claims that the SVR has been disproven by this progress and that it no longer provides a useful, theoretically sound, and empirically supported model of reading. Furthermore, we reject the claims that the proposed alternative to the SVR offered by Duke and Cartwright (2021) is superior (either theoretically or empirically), and that it represents an advancement in pedagogical utility. In this comment on Duke and Cartwright’s (2021) central claims, we discuss (1) the authors’ view of the SVR (addressing issues about what it models, the distinctions it embodies between proximal and distal factors, and its utility for practitioners); (2) the authors’ claims that three advances in reading research invalidate the SVR (namely, the causes of reading difficulty within and beyond the SVR’s two factors of word recognition and language comprehension, 1 the overlap between measures of these two factors and the bridge skills claimed to be supported on the basis of such overlap, and the role of active self‐regulation in reading); and (3) the authors’ summary conclusion that the SVR, and any other expanded models of reading based on it, must be rejected because of these advances.…”
contrasting
confidence: 64%
“…Duke and Cartwright (2021) argue that the simple view of reading (SVR) be replaced so that education professionals can gain an up‐to‐date picture from the science of reading about what reading requires and where instruction must be focused: “Given the enormous popularity of the SVR as the guiding framework for the current ‘science of reading’ movement, many practitioners have not yet been offered other models that can more productively guide their practice” (p. 15). Without these, the authors claim, education professionals will not be able to avoid the misleading (and presumably harmful) guidance stemming from a dated SVR, for example, through its failing to show that “reading difficulties can have causes beyond word recognition and language comprehension .…”
mentioning
confidence: 99%
“…More studies are needed to verify the SVR’s adequacy in adult typical readers, and they should include proposals for additional inclusions as a way of increasing the percentage of explained variance of reading comprehension. Recent studies have suggested the inclusion of higher-order cognitive skills (e.g., inference making, perspective-taking, and comprehension monitoring; Kim, 2017 , 2020 ), text characteristics (e.g., sentence length and frequency of the words; Francis et al, 2018 ), and variables of self-regulation when reading (e.g., motivation, engagement, and the use of reading strategies; Duke and Cartwright, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both the SVR and SVW represent one view on literacy, describing "proximal causes of individual differences in reading" (Tunmer & Chapman, 2012, p. 454). Listening comprehension and decoding may appear comprehensive in the explanation of reading comprehension problems, yet there are also studies that documented a portion of their sample with generally typical decoding and listening comprehension skills that struggled with reading comprehension (Duke & Cartwright, 2021). Other models add self-regulation skills (akin to the SVW) and also include constructs that might account for the lack of independence between decoding and listening comprehension.…”
Section: Limitationsmentioning
confidence: 99%
“…Other models add self-regulation skills (akin to the SVW) and also include constructs that might account for the lack of independence between decoding and listening comprehension. Semantic and morphological skills, reading fluency, and cognitive flexibility applied to letter/sound associations could account for this relationship (Duke & Cartwright, 2021).…”
Section: Limitationsmentioning
confidence: 99%